The Principles of Cooperative Learning in an Oral Communication Course in English: A Descriptive Analysis - Zúñiga Vargas, Juan Pablo (2014)
This article reports on the findings of a research conducted to describe the occurrence and effect of the principles of Cooperative Learning in an oral communication course in English for sophomores during one semester at a public university in Costa Rica. To collect data for the study, three instruments were used, an interview for the professor of the group, a questionnaire for the students, and class observations. The data collected were triangulated by means of predetermined categories of analysis. Overall, the findings obtained indicate that the use of Cooperative Learning, in addition to the professor’s commitment to support her students to learn, has produced significant results.